2008
DOI: 10.3354/ab00040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of passive integrated transponder (PIT) tags in studies of sea urchins: caution advised

Abstract: We evaluated the effect of passive integrated transponder (PIT) tags on feeding, growth, movement and survival of the sea urchin Strongylocentrotus droebachiensis in field and laboratory experiments. In cages supplied with kelp, 80% of urchins (n = 74) retained their tag during an 80 d field experiment. At the end of the experiment, tagged individuals had a lower growth rate (by 42%), lower gonad index (by 23%), lower survival rate (by 30%), and took longer to right themselves (by 30%) than untagged control ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…These results are consistent with those obtained in the framework of fish research (Moore et al, 1990;Newby et al, 2007) and sea urchins (Lauzon-Guay & Scheibling, 2008). Another essential behavioral pattern, courtship, occurred frequently during our experiment.…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with those obtained in the framework of fish research (Moore et al, 1990;Newby et al, 2007) and sea urchins (Lauzon-Guay & Scheibling, 2008). Another essential behavioral pattern, courtship, occurred frequently during our experiment.…”
Section: Discussionsupporting
confidence: 82%
“…Tagging animals has been over time a useful tool to understand important aspects about behaviour and population dynamics (Olson & Newton, 1979;Pollock et al, 1990;Mowat & Strobeck, 2000;Williams et al, 2002;Shiell, 2006;Lauzon-Guay & Scheibling, 2008;Martínez et al, 2013). In these kinds of studies, a correct identification and high tag retention are essential to achieve a successful analysis (Caswell, 2001;Amstrup et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Many invertebrate species have a hardened exoskeleton, which is often moulted; a marker would need to be internal to be useful in any long-term studies (Reichling & Tabaka 2001). Additionally, it is difficult to attach tags externally, and to limit the detrimental effects of internal tags to animals in the invertebrate size range (Lauzon-Guay & Scheibling 2008). For example, Lauzon-Guay & Scheibling (2008) found that, on sea urchin, applying a PIT tag had a detrimental effect on all measures of performance, activity and survival in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is difficult to attach tags externally, and to limit the detrimental effects of internal tags to animals in the invertebrate size range (Lauzon-Guay & Scheibling 2008). For example, Lauzon-Guay & Scheibling (2008) found that, on sea urchin, applying a PIT tag had a detrimental effect on all measures of performance, activity and survival in the field. Bubb et al (2002) established that if PIT tags were inserted too close to the ventral nerve cord within the abdominal musculature of crayfish, the tagging process could be fatal for the animal.…”
Section: Introductionmentioning
confidence: 99%